Photosynthetic and morphological characters of leaves of the annual and biennial Salvia sclarea biotypes - Mihalik, Erzsébet (Acta Biologica Szegediensis, 2005)
The leaf anatomy, the CO2 assimilation rate, the photosynthetic pigment content and the chlorophyll fluorescence has been studied in young and old leaves of the biennial and annual biotypes of Salvia sclarea plants. The structure of the mesophyll of all leaves of both biotypes resembled to the „shade plants”. The values of the CO2 assimilation of young leaves however represented typical light leaf character with significantly higher saturation light intensity than that of the old leaves. According to our preliminary results it proved that the chlorophyll fluorescence characters (Fv/Fm and ETR) indicated moderate damage in the photosystem II of the young leaves. The increased NPQ of the same plant parts represented increased efficiency of heat dissipation and hence, greater photoprotection capacity.